2012
DOI: 10.1177/0003122412440802
|View full text |Cite
|
Sign up to set email alerts
|

School Context and the Gender Gap in Educational Achievement

Abstract: and the 2010 RC28 conference in Haifa, Israel for helpful comments and suggestions. We thank the Institut zur Qualitätsentwicklung im Bildungswesen (IQB) for providing access to the data and Prof. Rainer Lehmann for his help with the ELEMENT data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
279
4
9

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(309 citation statements)
references
References 40 publications
17
279
4
9
Order By: Relevance
“…In a recent and more methodologically rigorous quasi-experimental study, Legewie and DiPrete (2012) found a similar effect with the data on socio-economic composition and reading test scores of pupils in some elementary and upper-secondary schools in Berlin. Generally, girls did better in reading than boys.…”
Section: Literature Reviewsupporting
confidence: 72%
See 2 more Smart Citations
“…In a recent and more methodologically rigorous quasi-experimental study, Legewie and DiPrete (2012) found a similar effect with the data on socio-economic composition and reading test scores of pupils in some elementary and upper-secondary schools in Berlin. Generally, girls did better in reading than boys.…”
Section: Literature Reviewsupporting
confidence: 72%
“…Second, we look at the school-level correlates of the gender gap in math, such as school location, type and size. Following previous studies (Entwisle et al, 1994;Legewie and DiPrete, 2012), we hypothesize that the size of the gap may vary across schools with different characteristics. In particular, boys may do comparatively better in more academically oriented schools, with a more socially privileged student body.…”
Section: Research Questions Data and Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Several reasons for this gender gap in achievement are suggested, including home and school/classroom environment, socio-economic factors, peer culture, gender differences in attitudes towards school work (Warrington, Younger, & Williams, 2000), and degree of selfdiscipline (Duckworth & Seligman, 2006). Consequences are a higher degree of special education and higher dropout rates among men (Legewie & DiPrete, 2012), which lead to a range of possible negative concerns related to work status, income, behaviour, and quality of life (Belfield & Levin, 2007).…”
Section: Demographic Factorsmentioning
confidence: 99%
“…If this number was representative of any sort of reality, this would mean that boys are on average a little more successful in school than girls. This is not the case in Quebec nor in most industrialized countries (Legewie & DiPrete, 2012). …”
Section: Revue Des Sciences De L'éducation De Mcgill • Vol 52 N O 1 mentioning
confidence: 95%